Evaluation of 3D biomimetic microcarriers for enhancing therapeutic efficacy of human umbilical cord mesenchymal stem cells in psoriasis treatment - Li, XueMei; Chen, YanMei; Cai, JiaWei; Huang, YuQiong; Chen, XiangLong; Yu, MingYu; Fu, Li; Chai, Bao; Zhang, Cheng; Zhang, ZhiYong; Chen, HongXiang (Frontiers in Immunology, 2026)
Mesenchymal stem cells (MSCs) hold promise for regenerative medicine due to their unique biological properties, including self-renewal and multi-lineage differentiation potential. Conventional two-dimensional (2D) culture systems may hinder therapeutic efficacy due to challenges in maintaining quality and producing a sufficient quantity of cells for clinical applications. This study aimed to evaluate the influence of a three-dimensional (3D) microcarrier-bioreactor system on the biological characteristics of human umbilical cord MSCs (hUC-MSCs) and their potential therapeutic efficacy in a psoriasis mouse model. The 3D microcarrier-bioreactor system was observed to improve hUC-MSCs attachment and proliferation while preserving genetic stability, characteristic surface marker expression, non-tumorigenic properties, and differentiation potential, consistent with outcomes from 2D cultures. Moreover, the 3D-hUC-MSCs demonstrated enhanced proliferation, stemness, immune function, and cell viability compared to those cultured in 2D systems.In vitro experiments demonstrated that 3D-hUC-MSCs supernatants effectively suppressed IL-17A-induced NF-κB signaling in keratinocytes. In vivo, 3D-hUC-MSCs significantly reduced IMQ+IL-23-induced psoriasis-like skin inflammation by reducing immune cell infiltration and inhibiting IL-17-associated inflammatory pathways. Transcriptomic analysis revealed that 3D-hUC-MSCs modulated signaling pathways associated with inflammation and innate immune responses. Our findings suggest that the 3D microcarrier-bioreactor system holds promise as a strategy to enhance the therapeutic potential of hUC-MSCs, particularly in the treatment of immune-mediated disorders such as psoriasis.